Anatomy of the Superior and Inferior Labial Arteries Revised: An Ultrasound Investigation and Implication for Lip Volumization. (29th May 2020) - Cotofana, Sebastian; Alfertshofer, Michael; Schenck, Thilo L; Bertucci, Vince; Beleznay, Katie; Ascher, Benjamin; Lachmann, Nirusha; Green, Jeremy B; Swift, Arthur; Frank, Konstantin
Abstract: Background: Lips are considered a key element of facial attractiveness due to their central position in the face and their elemental role in verbal and nonverbal communication. Objectives: The authors sought to provide clinically relevant information on the 3-dimensional pathway of the superior and inferior labial arteries within the lips to increase safety during labial soft tissue filler injections. Methods: The study enrolled 41 healthy volunteers with a mean age of 26.17 ± 9.6 years and a mean body mass index of 23.09 ± 2.3 kg/m 2 . Ultrasound imaging was performed at 6 different locations. The position of the labial arteries within the lips, depth of the arteries, cranio-caudal location of each artery in relation to the vermilion border, and diameter of the superior/inferior labial arteries were recorded. Results: The most frequent location of both the superior and inferior labial arteries was the submucosal plane (58.5%) followed by intramuscular (36.2%) and subcutaneous (5.3%) planes. The depth of the superior labial artery in the upper lip was 5.6 ± 0.13 mm, whereas the depth of the inferior labial artery in the lower lip was 5.2 ± 0.14 mm. Both arteries were more frequently located within the red lip: upper lip (83% vs 18.7%) and lower lip (86.2% vs 13.8%). In the midline, the artery coursed within the red lip in all investigated volunteers. Conclusions: Clinically, results of this study favor a superficial injection plane for lip volumization procedures. A perpendicular approach to the lip (coming from the cutaneous lip) might increase safety because the artery is located most frequently within the red lip.